2014
DOI: 10.1371/journal.pone.0084578
|View full text |Cite|
|
Sign up to set email alerts
|

Diatoms: A Novel Source for the Neurotoxin BMAA in Aquatic Environments

Abstract: Amyotrophic lateral sclerosis (ALS) or Lou Gehrig’s disease is a neurological disorder linked to environmental exposure to a non-protein amino acid, β-N-methylamino-L-alanine (BMAA). The only organisms reported to be BMAA-producing, are cyanobacteria – prokaryotic organisms. In this study, we demonstrate that diatoms – eukaryotic organisms – also produce BMAA. Ultra-high-performance liquid chromatography coupled with tandem mass spectrometry revealed the occurrence of BMAA in six investigated axenic diatom cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 38 publications
5
134
0
Order By: Relevance
“…Commonly used derivatisation techniques in combination with LC-MS/MS analysis are AQC (e.g. [34,97,98]), propyl chloroformate (e.g. [91,99]) and dansyl chloride [100,101]), see Box 1.2 for explanation of AQC derivatised LC-MS/MS analysis.…”
Section: Analytical Methods For Bmaa Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Commonly used derivatisation techniques in combination with LC-MS/MS analysis are AQC (e.g. [34,97,98]), propyl chloroformate (e.g. [91,99]) and dansyl chloride [100,101]), see Box 1.2 for explanation of AQC derivatised LC-MS/MS analysis.…”
Section: Analytical Methods For Bmaa Analysismentioning
confidence: 99%
“…The only study so far on BMAA production by cyanobacteria [99] does not provide evidence as the 5 experimental setup is flawed, there is too little evidence for correct BMAA identification and not all results are presented (Appendix A5.6). Diatoms might also be BMAA producers, as one study has shown that axenic diatom cultures contain BMAA [98]. Taken together, only two studies have identified cyanobacteria and diatoms as possible BMAA producers, but their findings have not yet been confirmed by other, independent laboratories.…”
Section: Presence Of Bmaa In Aquatic Ecosystemsmentioning
confidence: 98%
See 3 more Smart Citations